Combining lung ultrasound and Wells score for diagnosing pulmonary embolism in critically ill COVID-19 patients - Zotzmann, Viviane; Lang, Corinna N.; Wengenmayer, Tobias; Bemtgen, Xavier; Schmid, Bonaventura; Müller-Peltzer, Katharina; Supady, Alexander; Bode, Christoph; Dürschmied, Daniel; Staudacher, Dawid (Journal of thrombosis and thrombolysis, 2021)
Subpleural consolidations have been found in lung ultrasound in patients with COVID-19, possibly deriving from pulmonary embolism (PE). The diagnostic utility of impact of lung ultrasound in critical-ill patients with COVID-19 for PE diagnostics however is unclear. We retrospectively evaluated all SARS-CoV2-associated ARDS patients admitted to our ICU between March 8th and May 31th 2020. They were enrolled in this study, when a lung ultrasound and a computed tomography pulmonary angiography (CTPA) were documented. In addition, wells score was calculated to estimate the probability of PE. The CTPA was used as the gold standard for the detection of PE. Twenty out of 25 patients met the inclusion criteria. In 12/20 patients (60%) (sub-) segmental PE were detected by CT-angiography. Lung ultrasound found subpleural consolidations in 90% of patients. PE-typical large supleural consolidations with a size ≥ 1 cm were detectable in 65% of patients and were significant more frequent in patients with PE compared to those without (p = 0.035). Large consolidations predicted PE with a sensitivity of 77% and a specificity of 71%. The Wells score was significantly higher in patients with PE compared to those without (2.7 ± 0.8 and 1.7 ± 0.5, respectively, p = 0.042) and predicted PE with an AUC of 0.81. When combining the two modalities, comparing patients with considered/probable PE using LUS plus a Wells score ≥ 2 to patients with possible/unlikely PE in LUS plus a Wells score < 2, PE could be predicted with a sensitivity of 100% and a specificity of 80%. Large consolidations detected in lung ultrasound were found frequently in COVID-19 ARDS patients with pulmonary embolism. In combination with a Wells score > 2, this might indicate a high-risk for PE in COVID-19.